Pemaknaan Spiritual melalui Sholat Hajat dan Tawassul dalam Pemulihan Psikologis Narapidana - Fany Imanda; Yohandi Yohandi; Akhmad Husam Sulaiman (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
This research aims to understand deeply the process of spiritual meaning of inmates through the intervention of counseling based on Islamic rituals, namely prayer and tawassul, in an effort to overcome emotional distress. The initial formulation includes all functions contained in the System Needs Specification (SRS) document, while the final formulation includes all the functions contained in the SRS, but with the addition or change that occurs during the research process. This study used a qualitative approach with the study subjects in the form of female inmates with the initials of the hospital, aged 30 years, widow status, have three children, who underwent a coaching period in the Class IIA Banyuwangi Prison. Data collected through in-depth interviews, observations of worship behavior, and analysis of official documents of Lapas. The results showed that the hospital's emotional distress stemmed from the rejection of her father and brother, which triggered chronic guilt, damage to moral identity, spiritual disturbance, and reliance on external validation. Implementation of prayer and tawassul in counseling is able to create a safe cathartic space, stimulate the shift of locus of control from external to internal-spiritual, as well as form a proactive religious coping mechanism. The practice of prostration in prayer requires controlled emotional release, while tawassul reinforces the hope, sense of acceptance, and confidence in divine help. After a week of consistent practice, the hospital showed significant improvements in emotional stability, self-confidence recovery, changes in self-confidence, and a more mature orientation of life meaning. The findings confirm that spiritual counseling based on Islamic rituals is an effective and contextual approach in the rehabilitation of inmates in Indonesia, as it not only strengthens aspects of religiosity, but also restores holistic and sustainable psychological well-being.